Stimulating teachers' team performance through team-oriented HR practices: the roles of affective team commitment and information processing. Issue 5 (9th March 2019) - Bouwmans, Machiel; Runhaar, Piety; Wesselink, Renate; Mulder, Martin
Abstract: Teams of teachers are increasingly held accountable for the quality of education and educational reforms in vocational education and training institutions. However, historically teachers have not been required to engage in deep-level collaboration, thus team-oriented HR practices are being used to promote teamworking in the sector. This paper examines the relationship between team-oriented HR practices and team performance in terms of innovation and efficiency via teachers' affective team commitment and engagement in information processing. To examine these associations, a team-oriented HRM research instrument was developed and validated based on the ability-motivation-opportunity model ( N  = 970, 130 teams) and hypothesised associations were examined using multilevel structural equation modelling ( N  = 704, 70 teams). The results show positive relationships between the team-oriented HR practices of recruitment, team development, team evaluation and teamwork facilitation, and team innovation. Additionally, all practices except team development were positively related to team efficiency. The relationships between team-oriented HR practices and these team performance indicators were often partially or fully mediated by affective team commitment and information processing. Because affective team commitment and information processing sometimes only partially mediated the links between team-oriented HR practices and team performance, other underlying mechanisms await identification.